2007
DOI: 10.3844/ajassp.2007.192.196
|View full text |Cite
|
Sign up to set email alerts
|

Income Distribution and Health Status: Econometric Evidence from OECD Countries

Abstract: This research note, using a cross-sectional sample consisting of 27 Organization for Economic Co-operation and Development countries (OECD) for the reference year 2002, empirically examines the relationship between health status as measured by infant mortality and the degree of income inequality, given the effect of certain controlled variables. The empirical findings based on the estimation by robust econometric methods, show that in these countries, per capita real gross domestic product, the number of docto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The only exception is higher-educated people who are less likely to visit a dentist than lower-educated as physicians' density increases. As some studies have shown (Murthy, 2007), the greater the physicians' density, the better the health status.…”
Section: Discussionmentioning
confidence: 99%
“…The only exception is higher-educated people who are less likely to visit a dentist than lower-educated as physicians' density increases. As some studies have shown (Murthy, 2007), the greater the physicians' density, the better the health status.…”
Section: Discussionmentioning
confidence: 99%
“…One of the important factors that have been theoretically identified in the context of population health is the degree of income inequality (Murthy 2007). The relative income hypothesis states that health status is adversely influenced by the degree of income inequality.…”
Section: Continued)mentioning
confidence: 99%
“…Previous operations of government sector on monks' health care could have not been resolved problems due to lacking of concrete participation of communities and local administrative organizations, integrated operations from related agencies both of government and private sector (Hathirat, 1983;Goslinga, 1998;Ramsay et al, 2000;Miller et al, 2009;Murthy, 2007). These effected to the development of sustainable health care by themselves and needed to have a research with objectives to study body of knowledge, current conditions and problems and to develop monks' holistic health care models by community participation in central region of Thailand.…”
Section: Introductionmentioning
confidence: 99%